1995
DOI: 10.3171/jns.1995.83.2.0336
|View full text |Cite
|
Sign up to set email alerts
|

Experimental chronic compressive cervical myelopathy: effects of decompression

Abstract: Twelve dogs developed a delayed onset of neurological abnormalities from chronic cervical cord compression that was characteristic of myelopathy. The animals were divided into two groups and matched according to degree of neurological deficit. Six animals underwent decompression through removal of the anteriorly placed compressive device. Throughout the experiment, serial neurological examinations and somatosensory evoked potential studies were performed on each animal. Spinal cord blood flow measurements were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
3

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 33 publications
2
35
0
3
Order By: Relevance
“…However, as the degree of compression increases, there is a rapid reduction of spinal cord blood flow leading to ischemia once the autoregulatory limits have been exceeded. Pathological examination revealed irreversible changes, including flattening of the anterior horn, disappearance and necrosis of anterior horn cells in the grey matter, and demyelination and axonal degeneration in the white matter [8,12]. The mean duration of spinal cord compression in these animal studies was 10 months, which is close to the mean duration of symptoms before diagnosis in clinical reports on spinal meningiomas.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…However, as the degree of compression increases, there is a rapid reduction of spinal cord blood flow leading to ischemia once the autoregulatory limits have been exceeded. Pathological examination revealed irreversible changes, including flattening of the anterior horn, disappearance and necrosis of anterior horn cells in the grey matter, and demyelination and axonal degeneration in the white matter [8,12]. The mean duration of spinal cord compression in these animal studies was 10 months, which is close to the mean duration of symptoms before diagnosis in clinical reports on spinal meningiomas.…”
Section: Discussionsupporting
confidence: 47%
“…Whether acute or chronic, spinal cord compression damages neural tissue both by mechanical and vascular mechanisms. Experimental subacute and chronic compressive myelopathy has shown that the first modification is impairment of somatosensory evoked potentials, which is attributable to a mechanical factor [7,8,12]. However, as the degree of compression increases, there is a rapid reduction of spinal cord blood flow leading to ischemia once the autoregulatory limits have been exceeded.…”
Section: Discussionmentioning
confidence: 99%
“…In elderly Japanese CSM patients, the rate of occurrence of dynamic factors, such as instability of the vertebral column [1,[6][7][8]29], was shown to be higher than for static factors, such as developmental canal stenosis [24], by radiological analysis [26]. Furthermore, CSM patients 65 years and older with spondylolisthesis had a high incidence of degenerative spondylolisthesis (DS) at C3-C4 or C4-C5 [14].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment of mild and moderate forms of SCM in the present study design, comprising the patients with no or very slow, insidious progression and a relatively long duration of symptoms, did not show better results than conservative treatment over the 2-year follow-up. ported experimentally [16]. Many important variables, however, play a role in a clinical situation that could be different from the experimental conditions in animals.…”
Section: Introductionmentioning
confidence: 99%